PTU-085 A NOTCH1-Driven Secretome Switch Modulates Immune Surveillance In Ras-Induced Senescence. (17th August 2016) - Hoare, M; Ito, Y; Kang, T-W; Menon, S; Salama, R; Zender, L; Narita, M
Abstract : Introduction: Oncogene-induced senescence (OIS) is an intrinsic tumour suppressor mechanism, but its impact on tumorigenesis is largely dependent on the nature of the senescence-associated secretory phenotype (SASP). Major components of the SASP include TGFβ1 and pro-inflammatory cytokines, such as IL1, IL6, and IL8, that have pleiotropic context-dependent effects. Methods: We utilised the well validated ER:Ras G12V IMR90 HDF in vitro model which undergo Ras-induced senescence (RIS) with 4 OHT. Genetic manipulation was achieved through retroviral gene transfer; transcriptional profiling by mRNA-seq; validation through qPCR and immunoblotting. In vivo hepatocyte senescence was achieved through hydrodynamic tail-vein delivery of NRAS G12V -containing transposons. Results: We have demonstrated that NOTCH1, a highly conserved receptor is up-regulated in RIS. In contrast to the up-regulation of NOTCH1, downstream signalling is dynamically regulated: the cleaved, active intracellular domain of NOTCH1 (N1ICD) and NOTCH-target genes were transiently up-regulated at an early phase of RIS, but down-regulated at full senescence. The dynamic expression patterns of N1ICD and TGF-β1 expression were nearly identical, and inversely correlated with the cytokines, IL1 and IL8. Inhibition of NOTCH1 signalling, through expression of a dominant-negative form of the NOTCH1 binding partner MAML1, led to a reduction in TGF-β1, but increased IL1 and IL8 expression during RIS. In addition, ectopic restoration of N1ICD in established RIS cells drove reciprocal secretome changes with reduced IL1 and IL8 and increased TGF-β1, suggesting NOTCH1 signalling plays a critical role in secretome switching. Utilising an NRAS-drive hepatocyte senescence model, NOTCH1 was upregulated during RIS in vivo. Previously it has been shown that the SASP in RIS is critical for the immune-mediated clearance of senescent hepatocytes. Consistent with the enhancement of the pro-inflammatory secretome, co-delivery of the NOTCH inhibitor dnMAML1 with RAS, accelerated the infiltration of CD3+ T-cells into the liver and promoted the clearance of senescent hepatocytes. Restoration of N1ICD in hepatocyte RIS led to senescence bypass and tumour formation. Conclusion: The transition to RIS is correlated with a NOTCH1-mediated switch from a TGFβ-rich secretome to a proinflammatory secretome. Promotion of this proinflammatory secretome, through NOTCH inhibition enhances immune surveillance of senescent hepatocytes. This raises the possibility of therapeutically promoting the clearance of senescent cells in vivo. Disclosure of Interest: None Declared